Studi karakteristik sintesis bioplastik menggunakan bahan dasar ubi kayu dengan variasi penambahan selulosa nanas dan pengadukan - khairani; Irdoni; Idral Amri (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2019)
Bioplastic or biodegradable plastics are polymers that are composed of organic monomers found in starch and cellulose. The purpose of this research is to make bioplastics with use of raw material starch cassava and cellulose filler pineapple leaves, by varying the speed of stirring and the number of fillers, as well as knowing the nature of the bioplastic mechanics (Modulus Young, Elogenasi , Strong tensile), biodegradability, morphology and site. The methods on this research started from the preparation of raw materials, the manufacture of cellulose pineapple, the manufacture of cassava starch and the manufacture of bioplastics. The concentration of fillers used in the study was 0.3 grams, 0.6 grams, 0.9 grams, 1.2 grams and 1.5 grams in every 10 grams of starch, stirring variations of 200 rpm and 300 rpm. And obtained the best results in this study is bioplastic which has a strong tensile 13.24 Mpa, elongation 5.16%, modulus young 1072.83 Mpa, biodegrability of the land for 7 days, site 33.33%, obtained at a concentration of 1.5 grams cellulose and pineapple Stirring 300 rpm.